EDFA Application Research in WDM Communication Systems - Bobrovs, V.; Berezins, S. (Elektronika ir Elektrotechnika, 2013)
Characteristics of Erbium-Doped Fiber Amplifier are researched in this article. Amplification, noise figure and its dependences on different EDFA parameters are simulated and measured in 2.5 Gbit/s one channel transmission system. Simulation allows using EDFA amplifier with a variable length of fiber which would be impossible to realize in the real world. EDFA operation is executed in OptSim software environment and in experimental working model. Almost identical results indicate on high accuracy of simulation. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.3476